2015
DOI: 10.22452/mjs.vol34no1.9
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Cochlodinium Polykrikoides (Dinophyceae), a Harmful Algal Bloom (Hab) Species in the Coastal Waters of Peninsular Malaysia

Abstract: ABSTRAKCochlodinium polykrikoides di kenali sebagai 'fish-killer' . Di Malaysia, spesis ini telah direkodkan di Kota Kinabalu, Sabah, Kepulauan Borneo. Setakat ini, C. polykrikoides tidak direkodkan hadir di perairan Semenanjung Malaysia. Tujuan kajian ini dijalankan adalah untuk mengenapasti kehadiran C. polykrikoides di Semenanjung Malaysia terutamanya di Tanjung Piandang, Kuala Kurau dan Kuala Gula, di perairan pesisir pantai Perak dan Selat Tebrau, Johor. Persampelan dijalankan sebanyak tiga kali di setiap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…However, the growth of M. polykrikoides is inhibited by a concentration of NH 4 (> 50 µM) (Lee 2008). However, a high concentration of ammonia (2.78-55.50 µM) was recorded during the first occurrence of M. polykrikoides in peninsular Malaysia (Harun et al 2015). However, a high concentration of phosphate (0.16-3.25 µM) was found during blooms of M. polykrikoides in Mexico (Gárate-Lizárraga et al 2004) (Table 3).…”
Section: End Of Experiments (Um)mentioning
confidence: 98%
See 1 more Smart Citation
“…However, the growth of M. polykrikoides is inhibited by a concentration of NH 4 (> 50 µM) (Lee 2008). However, a high concentration of ammonia (2.78-55.50 µM) was recorded during the first occurrence of M. polykrikoides in peninsular Malaysia (Harun et al 2015). However, a high concentration of phosphate (0.16-3.25 µM) was found during blooms of M. polykrikoides in Mexico (Gárate-Lizárraga et al 2004) (Table 3).…”
Section: End Of Experiments (Um)mentioning
confidence: 98%
“…In Malaysia, M. polykrikoides was first observed in the Sepanggar Bay, Sabah in 2005(Anton et al 2008) before it was reported in peninsular Malaysia in 2013 (Harun et al 2015). Based on large the subunit ribosomal RNA gene (LSU rDNA), M. polykrikoides found in Malaysia belong to the American ribotype (Iwataki et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Blooms of M. polykrikoides reoccurred in Perak in 2013, resulting in substantial losses for local fishermen [120]. The frequency of fish kill events increased significantly starting from 2014.…”
Section: Fish Kill Events In Malaysiamentioning
confidence: 99%
“…HAB species that caused mass fish mortality have been well documented in the coastal waters of Malaysia . These included the raphidophytes Chatonella B.Biecheler (Choo 1994, Lum et al 2021, the dinophytes Ceratium (Tripos) furca (Lemmerman) Jörgesen (unpublished data), Margalefidinium polykrikoides (Margalef) F.Gómez, Richlen & D.M.Anderson (Anton et al 2008, Harun et al 2015, Mohd Razali and Shahuntalla 2017, Noctiluca scintillans (Macartney) Kofoid & Swezy (Choo 1994, Mohd Razali et al 2016, and Karlodinium australe Salas, Bolch & Hallegraeff (Lim et al 2014. Blooms of Margalefidiniun sp.…”
Section: Introductionmentioning
confidence: 99%